The Influence of Jigsaw Type Cooperative Models on Communication Skills of Elementary School Students - Dini Maielfi; Sisri Wahyuni (Postgraduate, University of Mataram, 2020)
This research is motivated by the low student communication skills caused by 1) when learning, students have not been able to convey their ideas either when discussing with friends, presentations, or when solving problems in learning; 2) students are shy to ask questions, tend to be silent, and when learning takes place the attention of students is not focused on learning or the other person; 3) students who are less academic yet able to convey the essence of learning if asked to become a tutor. This study aims to determine the impact of jigsaw on the communication skills of fourth-grade students at SDN 22 Kuranji Padang. This type of research is Pre-Experimental Design. The results of this study were obtained µ1 <µ2, (67.66 <82.05), with a significance of N-Gain 0.45 in the medium category. Then Ha is accepted. From the results of this study, it was proven that jigsaw had a significant impact on the communication skills of fourth-grade students of SDN 22 Kuranji, Padang city